The assessment of the stability of the corneal structure after LASIK correction of myopia by different optical zone diameters - Milivojević, Milorad; Petrović, Vladimir; Vukosavljević, Miroslav; Marjanović, Ivan; Resan, Mirko (Vojnosanitetski pregled, 2017)
Background/Aim. Enlargement of optical zone (OZ) diameter during laser in situ keratomileusis (LASIK) correction of myopia postoperatively improves the optical outcome, however, it also leads to the increased stroma tissue consumption – progressive corneal thinning. The aim of this investigation was to present the possibility of safe OZ enlargement without impairing the structural stability of the cornea, while obtaining an improved optical outcome with LASIK treatment of short-sightedness. Methods. Preoperative assessment of the cornea structure and prediction of the ablated stroma tissue consumption was conducted in 37 patients (74 eyes) treated for short-sightedness by means of the LASIK method. With the eyes that, according to their cornea structure, had the capacity for OZ diameter enlargement of 0.5 mm, LASIK treatment was performed within the wider OZ diameter of 7.0 mm compared to the standard 6.5 mm. The following two groups were formed, depending on the diameter of the utilized OZ: the group I (the eyes treated with the OZ 6.5 mm, n = 37) and the group II (the eyes treated with the OZ 7.0 mm, n = 37).  Results. No significant difference in the observed structural parameters of the cornea was detected between the groups of patients treated with different OZ diameters. The values of all the parameters were significantly bellow the threshold values for the development of postoperative ectasia. Conclusion. Diameter enlargement of the treated OZ, if there is a preoperative cornea capacity for such enlargement, will not impair the postoperative stability of the cornea structure, and will significantly improve the optical outcome.
Keywords: myopia; keratomileusis; laser in situ; ophthalmologic surgical procedures; cornea; tretmant outcome